From assistance to integrity: exploring the role of AI in academic communication across Russian and Turkish campuses - Sergeeva, Olga V.; Zheltukhina, Marina R.; Demir, Servet (Frontiers in Communication, 2025)
IntroductionThis paper investigates how 33 Turkish and 38 Russian university students perceive and experience artificial intelligence (AI) in scholarly communication. This study investigates students’ perspectives, experiences, and concerns regarding AI use in educational settings. Three main areas of inquiry are addressed: general views and experiences with AI technology, effects on academic communication and teamwork, and evaluation of AI-generated work in terms of academic integrity and plagiarism.MethodsThe study participants were 71 university students, consisting of 33 Turkish students and 38 Russian students. Data was collected through open-ended questionnaires. Qualitative material was examined using six-stage theme analysis system.ResultsOur findings reveal both shared and divergent perspectives among Turkish and Russian students regarding AI’s role in their educational environment. Students from both countries recognize AI’s significant potential to streamline academic tasks and enhance access to information. However, they also voice apprehensions over its influence on critical thinking abilities and academic honesty. Turkish students exhibited a predominantly favorable outlook toward the collaborative capabilities of AI, but Russian students placed greater emphasis on apprehensions over privacy and data security.DiscussionThe study highlights the complex interplay between the benefits and challenges of AI in educational environments. Students in both countries encounter ethical issues, namely plagiarism and the authenticity of AI-generated content. Our research highlights the importance of clearly defined institutional regulations and educational initiatives to offer guidelines for the use of AI in academia. This comparative study offers a fascinating analysis of the cultural factors influencing AI applications in higher education. It adds to the ongoing worldwide conversation about how technology impacts future educational plans.